Current Status of Synthetic and Biological Grafts for Hemodialysis - Patel, Purav P.; Altieri, Maria; Jindal, Tarun R.; Guy, Steven R.; Falta, Edward M.; Elster, Eric A.; Hurst, Frank P.; Sidawy, Anton N.; Jindal, Rahul M. (IntechOpen, 2011)
None